Exploring the Role of Planned Happenstance Skills in Shaping Career Adaptability Among High School Students - Nurul Izzah Subhan; Muhammad Nur Wangid (STAI Hubbulwathan Duri, 2025)
Planned happenstance skills are crucial for thriving in an ever-changing environment, fostering adaptability in the face of uncertainty—an essential quality in today’s workforce. This study explores the role of planned happenstance skills as predictors of career adaptability among high school students, focusing on identifying the most influential dimensions. The study employed a quantitative approach, hypothesizing that (1) planned happenstance skills positively predict career adaptability, and (2) persistence contributes more significantly than other dimensions. A sample of 79 high school students in Wajo Regency was selected via simple random sampling. Data were collected using validated questionnaires measuring planned happenstance skills and career adaptability. Wolfowitz applied product-moment correlation to data analysis. Findings revealed a moderate positive correlation (r = 0.549, p 0.05), indicating that higher planned happenstance skills are associated with greater career adaptability. Among the dimensions, persistence accounted for the largest contribution (38%) to career adaptability. These results suggest that persistence is a critical factor in fostering career adaptability, reflecting students' ability to maintain effort despite challenges. This study contributes to the limited quantitative research on the relationship between planned happenstance skills and career adaptability in high school contexts. By highlighting the predictive role of planned happenstance skills, particularly persistence, this study provides actionable insights for career education programs. Schools can enhance students’ adaptability through targeted interventions fostering curiosity, flexibility, perseverance, optimism, and risk-taking, preparing them for unexpected career challenges.